MUSLIM PARENTS STRATEGY TO OVERCOME ONLINE GAME ADDICTED TEENAGER - Adelia Puspita Sari; Retno Puji Rahayu; Jalaluddin. B (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2022)
The purpose of this study was to examine how muslim parents' strategies in dealing with children addicted to online games. The objects in the study were parents in children who used online games. Parents need to understand the impact of excessive use of online games. This type of research uses qualitative methods with phenomenological approaches, data sourced from primary data with questionnaire techniques or questionnaires involving 42 respondents. From the results of research conducted showed that the closeness of parents with children accompanied by spiritualism approach becomes a very important factor in reducing children's addiction in playing online games. Restrictions on facilities such as internet quotas are also often done by parents so that children do not drag on in playing online games. In addition, parents also apply strategies in their spiritual aspects to children such as reminding prayers and other worship.